Influences of sintering temperatures and crystallite sizes on electrochemical properties of LiNiPO4 as cathode materials via sol–gel route for lithium ion batteries - T. Subramaniam, Ramesh; Karuppiah, Rajammal; Kasi, Ramesh; Dhar Malingam, Sivakumar; Duraisamy, Navaneethan (Springer New York LLC, 2017)
Abstract: Acetates of lithium (LiC2H3O2) and nickel (NiC2H3O2) together with ammonium dihydrogen phosphate (NH4)H2PO4 were used as starting materials to prepare LiNiPO4 cathode materials via sol–gel technique. This simple and effective method of using distilled water as main solvent was assisted by small amount of oxalic acid. Final product was obtained after sintering process at temperatures of 500 °C, 600 °C, 700 °C, and 800 °C for 3 h. The peaks in X-ray diffraction patterns reveal ordered olivine structure of LiNiPO4 under Pnma space group. The surface morphologies as in field emission scanning electron microscopy images clearly showed complete formation of LiNiPO4 with uniform size distribution. Charge–discharge tests recorded initial discharge capacities of 97.3 mAh g−1 and 91.1 mAh g−1 for LiNiPO4 obtained at sintering temperatures of 700 and 800 °C respectively in the voltage range 2.5–4.5 V. Insitu carbon coating during synthesis improved electrochemical performances of LiNiPO4. Sintering temperature 700 °C produced smaller LiNiPO4 particles compared to 800 °C, which enables good capacity retention.